(Invited) GeSn Short-Wave Infrared Photodetectors. (18th August 2016) - Cheng, Buwen; Liu, Zhi; Zheng, Jun; Su, Shaojian; Zhang, Dongliang; Wu, Wenzhou; Xue, Chunlai; Wang, Qiming
Abstract : Ge photodetector is very success in the Si-based photonics. Butdue to the limitation of the bandgap, Ge photodetector can't beoperated at light wavelength longer than 1600nm. Theincorporation of Sn into Ge adjusts the band structures, andeffectively shrinks the bandgap relative to pure Ge. This makesGeSn photodetector a promising device for short-wave infraredlight detection (about 2000nm wavelength). In this paper, growthof GeSn alloys on Si and Ge substrates by MBE and sputtering willbe introduced. GeSn PIN photodetectors were fabricated by CMOScompatible process. The performance of the GeSn PDs, such asdark current, response spectra and quantum efficiency will bepresented and discussed.